2015
DOI: 10.5664/jcsm.4602
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Obstructive Sleep Apnea Syndrome in Dental Patients with Tooth Wear

Abstract: Bruxism is an oral pathology of interest not only for dentists but also for specialists in sleep disorders. Sleep bruxism (SB) has been associated with obstructive sleep apnea syndrome Study Objectives: To estimate the frequency of obstructive sleep apnea syndrome (OSAS) in dental patients with tooth wear, and to assess the role of dentists in the identifi cation of patients at risk of OSAS. Methods: Dental patients with tooth wear and treated with occlusal splint were prospectively recruited to perform sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 30 publications
(35 reference statements)
0
31
0
4
Order By: Relevance
“…The reasons for excluding studies after full‐text assessment were as follows: review ( n = 4); case report ( n = 1); no PSG is used to diagnose OSAS ( n = 1); survey ( n = 1); different target condition ( n = 2); no determination of the association between OSAS and SB ( n = 2); less than 10 patients ( n = 1); and no PSG is used to confirm SB diagnosis ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for excluding studies after full‐text assessment were as follows: review ( n = 4); case report ( n = 1); no PSG is used to diagnose OSAS ( n = 1); survey ( n = 1); different target condition ( n = 2); no determination of the association between OSAS and SB ( n = 2); less than 10 patients ( n = 1); and no PSG is used to confirm SB diagnosis ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…These authors concluded that patients with tooth wear had a high frequency of OSAS, and they found a positive association between tooth wear severity and the severity of the OSAS. Although they did not differentiate between chemical and mechanical tooth wear, the authors suggest that tooth wear assessment can be a tool to identify patients at risk for having OSAS . An explanation given by the authors is the possible association between OSAS and sleep bruxism.…”
Section: Methodsmentioning
confidence: 94%
“…A direct association between tooth wear and OSAS cannot be hypothesised. Amongst the included papers, only one publication described a possible indirect association between tooth wear and OSAS (Table ). These authors concluded that patients with tooth wear had a high frequency of OSAS, and they found a positive association between tooth wear severity and the severity of the OSAS.…”
Section: Methodsmentioning
confidence: 99%
“…O estudo piloto de Smith et al 30 mostrou que a frequência de SAOS em pacientes com desgaste dentário foi três vezes maior do que a população. Encontraram correlação positiva significativa entre a gravidade do desgaste dentário e a gravidade do SAOS, ou seja, quanto maior o número de eventos de apneia maior o desgaste dentário encontrado.…”
Section: Discussionunclassified